EFEKTIVITAS METODE SQ4R (SURVEY, QUESTION, READ, REFLECT, RECITE, REVIEW) DALAM PEMBELAJARAN MEMAHAMI TEKS FEATURE KELAS VII SMP NEGERI 1 SIDIKALANG TAHUN PEMBELAJARAN 2012/2013 - Edward Coco Priyono Pardede (Asas: Jurnal Sastra, 2012)
This study aims to determine the effectiveness of the method SQ4R(Survey, Question, Read, Reflect, Recite, Review) in learning to understand thetext feature class VII SMP Negeri 1 Sidikalang many as 253 people. Samplestaken as many as 74 people from the two classes, class of 37 people to 37 peoplefor the experiment and the control class.The method used in this study is an experimental method, which is todetermine the effectiveness of the teaching methods used. Data collection tool wasa written test in the form of multiple choices (multiple-choice).Learning outcomes using SQ4R (Survey, Question, Read, Reflect, Recite,Review) is in both categories with an average value of 72.97. When compared tolearning by teaching methods directly in the category of simply average value of55.10.Analysis of data management in this study using the test "t". Furthermore,the hypothesis derived from the test calculations thitung = 3.37 and TTable at 5%significance level = 1.67 and at 1% significance level = 2.39, with db = 74-2 = 72,used db closest to 72 . Hypothesis is accepted if to> TTable (1.67 <3.37> 2.39).Thus, the hypothesis is accepted. It states that the method SQ4R (Survey,Question, Read, Reflect, Recite, Review) is more effective to apply in learning tounderstand the text feature class VII SMP Negeri 1 Sidikalang learning year2012/2013.Keywords: Method SQ4R, text features,